(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2022)
The market for products and services delivered to the poor people of the world is huge. Consumers at the very bottom of the economic pyramid – those with per capita incomes of less than 1,500 – number more than 4 billion. But the success of multinational corporations in penetrating these low-income customers has been patchy at best, with most companies based in the developed world choosing to focus on the middle and upper income segments of the developing world.The business world failed to seize the opportunity at the bottom of the economic pyramid due to poor infrastructure, non-existent distribution channels, illiteracy etc that stifle the enthusiasm of companies in serving people living in poverty. Therefore the development in infrastructure has a great role to play in shaping the rural market in India. This paper looks at the various facets of infrastructure development and its impact on the rural market of India.